Mitochondrial Chaperones in the Brain: Safeguarding Brain Health and Metabolism? - Castro, José Pedro; Wardelmann, Kristina; Grune, Tilman; Kleinridders, André (Frontiers in Endocrinology, 2018)
The brain orchestrates organ function and regulates whole body metabolism by the concerted action of neurons and glia cells in the central nervous system. To do so, the brain has tremendously high energy consumption and relies mainly on glucose utilization and mitochondrial function in order to exert its function. As a consequence of high rate metabolism, mitochondria in the brain accumulate errors over time, such as mitochondrial DNA (mtDNA) mutations, reactive oxygen species and misfolded and aggregated proteins. Thus, mitochondria need to employ specific mechanisms to avoid or ameliorate the rise of damaged proteins that contribute to aberrant mitochondrial function and oxidative stress. To maintain mitochondria homeostasis (mitostasis), cells evolved molecular chaperones that shuttle, refold or in coordination with proteolytic systems, help to maintain a low steady-state level of misfolded/aggregated proteins. Their importance is exemplified by the occurrence of various brain diseases which exhibit reduced action of chaperones. Chaperone loss (expression and/or function) has been observed during aging, metabolic diseases such as Type 2 Diabetes (T2D) and in neurodegenerative diseases such as Alzheimer’s (AD), Parkinson’s (PD) or even Huntington’s (HD) diseases, where the accumulation of damage proteins is evidenced. Within this perspective, we propose that proper brain function is maintained by the joint action of mitochondrial chaperones to ensure and maintain mitostasis contributing to brain health, and that upon failure, alter brain function which can cause metabolic diseases.